2001
DOI: 10.1172/jci200111076
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial coupling factor 6 as a potent endogenous vasoconstrictor

Abstract: We demonstrated recently that coupling factor 6, an essential component of the energy-transducing stalk of mitochondrial ATP synthase, suppresses the synthesis of prostacyclin in vascular endothelial cells. Here, we tested the hypothesis that coupling factor 6 is present on the cell surface and is involved in the regulation of systemic circulation. This peptide is present on the surface of CRL-2222 vascular endothelial cells and is released by these cells into the medium. In vivo, the peptide circulates in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Recently, CF6 was shown to have multiple extracellular roles as a circulating hormone [1]. CF6 increases arterial blood pressure in rats, which is consistent with the high levels of CF6 seen in the plasma of patients diagnosed with hypertension [2].…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Recently, CF6 was shown to have multiple extracellular roles as a circulating hormone [1]. CF6 increases arterial blood pressure in rats, which is consistent with the high levels of CF6 seen in the plasma of patients diagnosed with hypertension [2].…”
supporting
confidence: 65%
“…CF6 is an endogenous inhibitor of prostacyclin synthesis that suppresses the synthesis of prostacyclin via inhibition of cytosolic phospholipase A2 [21]; moreover, injected CF6 induces an increase in arterial blood pressure [1]. Since CF6 is present on the surface of vascular endothelial cells and is released outside the cells by mechanical forces such as shear stress [22,23], hypertension may be involved in the increase in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that CF6 is present not only in the mitochondria but also on the surface of human vascular endothelial cells and is released outside of the cells by mechanical forces such as shear stress [4] and by tumor necrosis factor a (TNF-a) [5]. We further showed that CF6 is an endogenous inhibitor of prostacyclin synthesis in human vascular endothelial cells and functions as an endogenous vasoconstrictor peptide in rats [6,7]. More recently, we showed that circulating CF6 is elevated in human hypertension and modulated by salt intake presumably via reactive oxygen species (ROS) [8].…”
Section: Introductionmentioning
confidence: 99%